DAMPAK KEBIJAKAN HARGA DASAR PADA HARGA PRODUSEN, HARGA KONSUMEN DAN LUAS TANAM PADI: BELAJAR DARI PENGALAMAN MASA LALU - U. HADI, PRAJOGO (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
EFFECTS OF FLOOR PRICE POLICY ON PRODUCER AND CONSUMER PRICE AND AREA PLANTED OF RICE: LEARNING FROM THE PAST EXPERIENCES. The government has launched various policies so as to increase rice production, one of which was floor price for husked rice. From the results of the analysis employing regression methods and time series data of 1969-1999, the following conclusions may be drawn. Firstly, the floor price of husked rice tended to increase during the period under study. Secondly, a 10% increase in the floor price of husked rice resulted in a 9,75% increase in the producer price; and a 10% increase in the producer price brought about a 8,39% increase in the consumer price of milled rice and a 0,61% increase in area planted of rice. This indicates that an increase in the floor price directly increased the producer price and indirectly increased the consumer price and the area planted of rice. Finally, the government policy successfully stabilised the domestic prices, and even the producer price was more stable than the consumer prices. It is suggested that the floor price policy needs to be continued with sufficient considerations of farmer’s profit and the world (Bangkok) price of milled rice.
Keywords: Floor Price Policy, Producer and Consumer Price, Area Planted, Rice